Status of Spousal Violence Experienced Women and Its Consequences on Reproductive Health Outcome in Rural Nepal - Paudel, Manusha; Khanal, Prabha; Bhujel, Samjhana (Nepal Population Journal, 2026)
Spousal violence causes a broad range of serious public and reproductive health problems. Spousal violence is widely prevalent in Nepal but rarely addressed in reproductive and maternal health matters. The objective of This paper is to explore the significant differences between spousal violence experienced and non-experienced rural women based on their socio-demographic and reproductive characteristics. Data was based on Nepal Demographic and Health Survey (NDHS), 2016, a publicly available dataset from dhsprogram.com/data/. The study was limited to 1389 currently married rural women in Nepal. A total of 351 spousal violence-experienced women, and 1038 non-experienced women were included in this study. More than half of sexual violence experienced women (57%) were aged 20-34 years with the highest pregnancy loss (33.7%). No schooling percentage was considerably higher among spousal violence experienced women (92.4%) than non-violence experienced women (45%). Two third (39.9%) of spousal violence experienced women had severe physical violence and 27.6 percent had sexual violence. Half of the spousal violence experienced women did not use any FP method. Two-fifth of violence-experienced women agreed on the justification for statements regarding wives beating. Age group and husband's Level of education were significantly associated with induced abortion at 0.05 level. The higher percentage of pregnancy loss was found in sexual violence experienced women (41%), and they were statistically significant at a 0.05 level. Binary logistic regression showed that women who experienced at least one form of violence (OR =2.1, CI =1.050-4.253), physical violence, and severe physical violence (OR=2.1, CI= 1.190-3.532), were statistically significant at 0.05 level. Pregnancy losses were 1.4 times more likely to experience sexual violence experienced women at 95 percent confidence interval. Reproductive outcomes of spousal violence experienced women were the highest, and some were statistically significant. Hence, spousal violence is essential to incorporate into reproductive and maternal health to minimize spousal violence and deliver quality, inclusive and sustainable health services. Furthermore, family planning, pregnancy, and abortion-related programs should focus on sexual violence experienced women.